Envisioning radical food geographies: shared learning and praxis through the Food Justice Scholar-Activist/Activist-Scholar Community of Practice. Issue 3 (November 2020) - Reynolds, Kristin; Block, Daniel R.; Hammelman, Colleen; Jones, Brittany D.; Gilbert, Jessica L.; Herrera, Henry
Food justice scholarship and activism have coevolved and at times been intertwined over past decades. In some instances, there are clear distinctions between "scholarly" and "activist" activities. However, individuals, groups, and actions often take on characteristics of both, producing knowledge at multiple sociopolitical scales. Recognizing and building upon these dynamics is important for strengthening food justice work. This is especially salient in an era in which academia, including geography, seeks more public engagement, yet has a complicated history of appropriating and/or dismissing experience-based knowledge, exacerbating uneven power-knowledge dynamics. These topics are of direct relevance to geography and intersect with radical geography traditions through engagement in social and political action and putting socio-spatial justice theory into practice. Since 2014, a small-but-growing group of individuals interested in the intersections between scholarship, activism, and geography have cultivated a Food Justice Scholar-Activist/Activist-Scholar Community of Practice (FJSAAS). This article examines the evolution and praxes of FJSAAS focusing on power-knowledge and radical geographies. Based on an analysis of FJSAAS records and recollections of participants since its founding, we discuss challenges encountered, the broader relevance for similarly positioned communities of practice, and offer recommendations for those engaging in food justice scholarship, activism, and/or radical geography. We conclude that radical geographies, concepts of radical food geographies, and scholar-activist/activist-scholar praxis are mutually reinforcing in recognizing experience-based knowledge as part of envisioning and putting into place a more just food system.